Estudo das características físicas e químicas da cinza do bagaço de cana-de-açucar para uso na construção - Nunes, Igo Henrique Silva (2009)
The bagasse from sugar cane is one of the byproducts of sugar cane industry, as well as sucrose and straw. Currently the bagasse generated in the plant is consumed for energy production through co-generation, making the plant self-sustainable energy and in some cases, sale of spare energy to electricity. During the process of burning the bagasse of sugar cane in the furnaces of boilers, occurs the generation of residual ash. Polls indicate that the ashes of bagasse from sugar cane (CBC) have predominantly silica in its composition which, when ground into very fine particle size, has physical and chemical characteristics that can provide the material effect of filler and pozzolanic activity. By presenting the characteristics already confirmed, the CBC can be used as raw material in the partial replacement of Portland cement to produce mortars and concrete. This paper aims to present the physical and chemical characteristics of ash from bagasse from sugar cane in four plants located in the region of Maringá, to its application in the production of concrete. For this, first was a literature review for information on the experiences in Brazil, involving testing and benchmarking of ash. Then, the following tests were performed for characterization: moisture content, organic matter and organic carbon, particle size, density, specific surface, chemical composition, pozzolanic activity, rheology of cement and gray and mechanical properties of concrete made with gray. This research is to contribute to the implementation of the CBC as alternative material for application in construction as an example the study of concrete made with the ashes of bagasse of sugar cane to replace the part Portland cement.